2019
DOI: 10.1088/1361-6528/ab5a1a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast temporal-spatial dynamics of amorphous-to-crystalline phase transition in Ge2Sb2Te5 thin film triggered by multiple femtosecond laser pulses irradiation

Abstract: Studies have shown that the crystallization phase state of Ge 2 Sb 2 Te 5 (GST) can be reversibly modulated by femtosecond (fs) laser multiple pulses, which have excellent applications in reconfigurable multi-level operation fields. In this study, the temporal-spatial crystalline evolution dynamics of amorphous GST film is investigated during two fs laser pulses excitation through a pump-probe shadowgraph imaging technique. A quasi-amorphous phase state, which is different from that in the initial as-deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The samples annealed at different temperatures were also measured using the Raman system, as shown in Figure 3 . According to the characteristic peaks of GST [ 26 , 29 , 31 , 32 , 33 ], it can be seen that a broad peak at about 150 cm −1 (Peak A) results from the stretching vibrations of Te-Te bonds Sb m Te 3 (m = 1, 2) pyramidal units [ 31 ], and another peak at about 110 cm −1 (Peak B) is caused by the heteropolar bonds of GeTe 4 or GeTe 3 Ge [ 26 ] for the as-grown GST and films annealed at 150 °C for 30 min. The relative intensity of Peak A to Peak B is about 1.4 for the amorphous GST, while it decreases to around 1.31 for the films annealed at 150 °C for 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples annealed at different temperatures were also measured using the Raman system, as shown in Figure 3 . According to the characteristic peaks of GST [ 26 , 29 , 31 , 32 , 33 ], it can be seen that a broad peak at about 150 cm −1 (Peak A) results from the stretching vibrations of Te-Te bonds Sb m Te 3 (m = 1, 2) pyramidal units [ 31 ], and another peak at about 110 cm −1 (Peak B) is caused by the heteropolar bonds of GeTe 4 or GeTe 3 Ge [ 26 ] for the as-grown GST and films annealed at 150 °C for 30 min. The relative intensity of Peak A to Peak B is about 1.4 for the amorphous GST, while it decreases to around 1.31 for the films annealed at 150 °C for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and Gan [ 25 ] found that the carriers could be excited within 1 ps and recovered less than 3 ns. In addition, the ultrafast dynamics of amorphous and quasi-amorphous GST films were compared in pump–probe experiments, and the mechanism of the crystallization enhancement effect was proposed [ 26 ]. However, there were the amorphous, crystalline, and intermediate phase states in reversible phase transitions, which had multiple applications e.g., non-volatile memory, because the characteristics of these phase states were different [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, as the laser fluence was gradually increased, the dominated peak shifted to ~105 cm −1 with a weaker one at ~135 cm −1 . Interestingly, the peak at ~105 cm −1 was considered as a characteristic peak of crystallization [ 42 ]. Among these intermediate states, the peak intensity at ~105 cm −1 was gradually increased with the increase of laser energy.…”
Section: Resultsmentioning
confidence: 99%
“…In GST -coated opaline photonic crystals, light control mediated by interplay of Wood anomalies and 3D Bragg diffraction resonances was demonstrated [20,21]. Raman spectroscopy measurements were performed to reveal the detailed phase state of GST [23]. We conclude our short review by mentioning that in phase-change materials based on GST, it is possible to produce laser-induced periodic ripples which are formed by interference of the incident laser beam with the surface electromagnetic wave excited by this beam [22,24].…”
Section: Introductionmentioning
confidence: 95%
“…The optical properties of both three-dimensional metamaterials and metasurfaces based on GST, including transmission, reflection, absorption and Raman spectra, have been actively studied [12][13][14][15][16][17][18][19][20][21][22][23][24]. Transmission and absorption studies have focused on the mid-infrared region, where strong spectral changes were observed as a result of the phase transition between the amorphous and crystalline phases, which can be used for practical applications.…”
Section: Introductionmentioning
confidence: 99%